ANALISIS ASUHAN KEPERAWATAN PADA REMAJA PUTRI DENGAN PREMENSTRUAL SYNDROME (PMS) MELALUI INTERVENSI YOGA - Kandia Dwi Sartika Putri, (2022)
Female adolescent experience menstruation as a sign that they are sexually mature. Premenstrual syndrome (PMS) is a collection of symptoms that appear a few days before the arrival of menstruation, and often causes discomfort both physically and psychologically. Regular physical activity for at least 30 minutes per day can help relieve PMS symptoms. Yoga is one of the easy physical activities and non-pharmacological interventions to treat PMS symptoms. The purpose of writing this final scientific paper is to analyze nursing care for female adolescents with premenstrual syndrome (PMS) through yoga intervention. The yoga intervention was given to female adolescents for eight meetings and used five yoga poses. The results showed that there was a decrease in the level of PMS symptoms experienced by female adolescents, both in managed patients and resume patients, from moderate to severe symptom levels to mild to moderate symptom levels. Yoga intervention can be used as a non-pharmacological treatment to treat PMS symptoms with minimal or no side effects. Adolescents are expected to be able to use yoga as non-pharmacological intervention to treat PMS symptoms.